2019
DOI: 10.5114/reum.2019.90825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole body cryotherapy in patients with rheumatoid arthritis considering immune parameters

Abstract: Objectives: Whole body cryotherapy (WBC) is widely used in inflammatory diseases of the joints, including rheumatoid arthritis (RA), but the mechanism(s) of its action is not fully understood. The aim of the study was to compare the effects of WBC and conventional rehabilitation (CR) on the clinical and immune status of RA patients. Material and methods: Rheumatoid arthritis patients were classified into 2 groups according to the rehabilitation method used: the study group (CT, n = 25) and control group (CR, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…In our study, also statistically significant changes in those parameters were observed . Analysis of the level of CRP after 4 weeks rehabilitation indicated no statistically significant decrease, what is confirmed in a study done by Sadura-Sieklucka [ 28 ]. However, Orlova’s [ 21 ] research covering a 6-month rehabilitation period shows that there was a statistically significant decrease in the CRP level which may suggest the need to extend the rehabilitation time.…”
Section: Discussionsupporting
confidence: 69%
“…In our study, also statistically significant changes in those parameters were observed . Analysis of the level of CRP after 4 weeks rehabilitation indicated no statistically significant decrease, what is confirmed in a study done by Sadura-Sieklucka [ 28 ]. However, Orlova’s [ 21 ] research covering a 6-month rehabilitation period shows that there was a statistically significant decrease in the CRP level which may suggest the need to extend the rehabilitation time.…”
Section: Discussionsupporting
confidence: 69%
“…There was also no significant impact on NGF level and nitric oxide production. Comparable results were presented by Sadura-Sieklucka et al (2019), where no differences in the concentrations of cytokine tested were observed in the serum of rheumatoid arthritis patients before and after cryotherapy. However, this is in contrast to the results obtained by Gizinska et al (2015), who presented that WBC exerted anti-inflammatory local and systemic effects.…”
Section: Discussionsupporting
confidence: 57%
“…In patients with RA that had undergone WBC, pain scores also seem to trend downwards, although there are contradicting findings. Both Giziń ska et al and Sadura-Sieklucka et al found that WBC (-110°C and -120 to -140°C, respectively) along with physical rehabilitation on patients with RA had a significant decrease in pain VAS, but results were not significantly different compared to the control group that only received physical rehab [12,29]. Giziń ska et al also reported a decrease in disease activity (DAS28) and improvements in the 50-m walk test after WBC, showing increases in objective measurements of pain, but again those results were not significantly different than the control group.…”
Section: Rheumatic Diseasesmentioning
confidence: 96%
“…For this reason, the outcomes in this review will primarily focus on pain measurements, such as the Visual Analogue Scale for pain (VAS), with supplementary evidence including range of motion (ROM) and disease activity, such as Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Disease Activity Score 28 (DAS28) among a few others. For example, the BASDAI has six questions for patients with AS regarding fatigue, spinal and peripheral joint pain, peripheral swelling, tenderness, and morning stiffness [28] and the DAS28 includes parameters such as swollen and tender joint count, global visual analogue scale measuring overall patient health, and erythrocyte sedimentation rate [13,29]. With these disease activity scores, a more generalized conclusion can be made as chronic pain can affect almost every aspect of a patient's life.…”
Section: Supportive Evidence On Pain Reduction and Adverse Effectsmentioning
confidence: 99%